Relationships of the Microbial Communities with Rumen Epithelium Development of Nellore Cattle Finished in Feedlot Differing in Phenotypic Residual Feed Intake - Silvestre, Antonio M. [UNESP]; Pinto, Ana Carolina J. [UNESP]; Schleifer, Werner F. [UNESP]; Miranda, Lidiane S. [UNESP]; Silva, Leandro A. F. [UNESP]; Casali, Daniel M. [UNESP]; Souza, Katia L. R. [UNESP]; Gasparini, Vanessa G. L. [UNESP]; Cruz, Gustavo D.; Suen, Garret; Millen, Danilo D. [UNESP] (MDPI, 2022)
The objective of this study was to examine the relationships among ruminal microbial community, rumen morphometrics, feeding behavior, feedlot performance, and carcass characteristics of Nellore cattle, classified by residual feed intake (RFI). Twenty-seven Nellore yearling bulls with an initial body weight (BW) of 423.84 ± 21.81 kg were fed in feedlot for 107 d in individual pens to determine the RFI phenotype. Bulls were categorized as high RFI (>0.5 SD above the mean, n = 8), medium RFI (±0.5 SD from the mean, n = 9), and low RFI (<0.5 SD below the mean, n = 10). At harvest, whole rumen content samples were collected from each bull to evaluate ruminal microbial community, including bacteria and protozoa. The carcass characteristics were determined by ultrasonography at the beginning and at the end of the experimental period, and behavior data were collected on d 88. As a result of ranking Nellore bulls by RFI, cattle from low-RFI group presented lesser daily dry matter intake (DMI), either in kilograms (p < 0.01) or as percentage of BW (p < 0.01) than high-RFI yearling bulls, resulting in improved gain:feed (G:F). However, variables, such as average daily gain (ADG), final BW, hot carcass weight (HCW) and other carcass characteristics did not differ (p > 0.05) across RFI groups. The eating rate of either dry matter (DM)(p = 0.04) or neutral detergent fiber (NDF) (p < 0.01) was slower in medium-RFI yearling bulls. For ruminal morphometrics an RFI effect was observed only on keratinized layer thickness, in which a thinner layer (p = 0.04) was observed in low-RFI Nellore yearling bulls. Likewise, Nellore yearling bulls classified by the RFI did not differ in terms of Shannon’s diversity (p = 0.57) and Chao richness (p = 0.98). Our results suggest that the differences in feed efficiency of Nellore bulls differing in phenotypic RFI should be attributed to metabolic variables other than ruminal microorganisms and epithelium, and deserves further investigation.
Keywords: 16S ribosomal RNA; Carcass; Feed efficiency; Nellore; Performance; Ruminal epithelium